A Multimodal Communicative Approach to the Analysis of Typography in Online English Learner's Dictionaries. (11th February 2022) - Hao, Junjie; Xu, Hai; Hu, Huilian
Abstract: The rise of online dictionaries has brought fundamental changes to dictionary typography. Using a multimodal communicative approach, this study aims to explore the current use of typography in online English learner's dictionaries in light of the transition from typography for print to typography for digital display. The approach and the analytical framework were developed on the basis of theories of multimodality, dictionary communication and typographic studies. Sample entry pages for the word panda, as well as the 'Word of the Day' sections in the 'Big Five' online English learner's dictionaries, have been used for case analyses. Typographic features were mainly identified using Whatfont, an extension of Google Chrome. Following a two-step procedure of identification and explanation, this study summarised the main features of the typography used in online English learner's dictionaries, considering the consistency of typefaces, a certain degree of variation, the use of colour, and the deployment of space. As an important mode for making meaning in dictionary communication, typography has representational, structural, interpersonal, and aesthetic functions. These functions show different dimensions of the communicative potential of dictionary typography.